Hydrodynamic coefficients and pressure loads on heave plates for semi-submersible floating offshore wind turbines: A comparative analysis using large scale models. (September 2015) - Lopez-Pavon, Carlos; Souto-Iglesias, Antonio
Abstract: Hydrodynamic forces on heave plates for a semi-submersible floating offshore wind turbine are discussed herein. A model of one of the platform columns has been built. This allows for the fitting of either a plain solid plate or the real heave plate prototype design. The latter is equipped with a vertical flap at its edge. The influence of the flap on the hydrodynamic coefficients is investigated through a results comparison with the plain solid one. The model plate diameter is 1 m, thus becoming, to the authors' knowledge, the largest for which results have been published. Results from experiments, in which added mass and damping coefficients have been measured, are presented. This experimental campaign also comprised the direct measurement of dynamic pressures on both heave plates, a fundamental magnitude for the structural design, which, until now, had not been experimentally explored for this type of system. For comparative reasons, numerical simulations were also conducted following common industry standards, both with a wide-spread frequency domain panel method (WADAM) and a RANS CFD commercial code (ANSYS CFX). Finally, results are compared with literature and consistent non-dimensionalizations are sought, with the aim of making these results useful for preliminary design purposes. The authors believe this research could benefit the offshore wind industry by improving the hydrodynamic design of the concept. Highlights: Tests with floating wind turbine platform large scale heave plate models conducted. Solid plain plate and prototype design (equipped with a vertical flap) tested. Damping has been found significantly smaller for the plate equipped with the flap. Pressure difference between bottom and top sides measured during motion. Pressure found similar between plain & prototype plate, appart from flap zone.